KETIDAK-BERLAKUAN IWADL DALAM PRAKTIK KHULU’ (TAFSIR AYAT-AYAT KHULU’) - Indana Af'idah (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2016)
Islam is a religion that upholds the dignity of a woman. Women in Islam have equal status with men. In the Qur'an there are many verses that mention that a woman has the same rights and obligations as men. Included in this are the rights issue became a subject in a divorce. Although not an independent force in the establishment of a decision, but Islam does not necessarily vote a mistake. The presence of the khul'a theory actually support the woman’s human freedom. By submitting a number of property as a ransom request, khul'a be something that should be taken into account before a woman actually execute it. However, unlike the case with ar-Rozi stating that it is not always khul'a filed by submitting iwadl. According to his view that interpretation of Surat Al-Baqarah verse 229 as the khul'a primary basis must be juxtaposed with the interpretation of two verses were: surah Al-Nisa verse 4 and 128. These two verses are stressing about the condition of women who must submit iwadl if he filed khul'a. From here it becomes clear that Islam has always put the balance of rights between men and women.